Budaya Antre sebagai Cermin Disiplin bagi Mahasiswa dalam Mengamalkan Pancasila - Eldiyano, Albertado Totto; Tumanggor, Raja Oloan; Simanjuntak, Jesica Febiani; Novianti, Allya Deby; Rosalia, Naurah Eka; Hasiva, Khaizza Rahma (Pusat Riset dan Inovasi Nasional, 2025)
Queuing culture is often perceived as a simple habit in daily life, yet in reality, it carries a deeper meaning in shaping individual character, particularly among university students. Standing in line is not merely about waiting for one’s turn, but also reflects discipline, respect for others’ rights, and a willingness to obey shared rules. This article discusses queuing culture as a reflection of student discipline in practicing the values of Pancasila. As the nation’s future generation, students hold a moral responsibility to become role models within society. By practicing queuing culture, they demonstrate the implementation of social justice, equality, and both personal and social responsibility. In the context of campus life, queuing behavior appears in various situations, such as waiting for administrative services, using shared facilities, or engaging in daily activities beyond the academic setting. Discipline in queuing trains students to be patient, orderly, and capable of self-control. These values are in line with the principles of Pancasila, especially in upholding humanity, unity, and social justice. Moreover, queuing culture serves as a means of internalizing public ethics that foster a more orderly and harmonious social environment. Therefore, queuing culture is not only a practical behavior but also a concrete manifestation of Pancasila in students’ everyday lives. Through this simple habit, students can cultivate self-discipline, respect the rights of others, and strengthen moral integrity. This article emphasizes that queuing practices can be considered a form of character education, relevant in shaping young generations who are disciplined, ethical, and consistently able to embody the values of Pancasila in social life.